Proposed Task-Based Materials for Writing Classes: A Case at University - Sundari, H; Febriyanti, R H; Saragih, G (KnE Social Sciences, 2018)
A task-based approach leads learners to focus on meaning instead of form and enhances their personal experiences in learning language. The present study aims to design task-based materials for writing classes at university. The research used a qualitative descriptive design through lecturers and students as respondents, and expert reviews. The research was conducted at a private university in Jakarta. As part of a research and development project, proposed task-based materials were developed based on needs assessment and a set of competencies underpinned by university vision and the graduate profile. The tasks were divided into task types, including pedagogical tasks, language exercises, and communicative activities, particularly for writing skills. Keywords: task-based materials, university students, writing class